Factors Affecting Earning Per Share (EPS) at PT. BANK MANDIRI Tbk Period 2018 - 2021 - Rasiman; Prasetia, Angga; Wibowo, Agung; Rizqi, M Nur (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2023)
This study aims to analyze the factors that influence Earning Per Share at PT Bank Mandiri Tbk. The period 2018 – 2021, which consists of factors that can affect EPS Return On Assets, Return On Equity, Net Interest Margin, Loan To Deposit Ratio, this analysis technique uses eviews V.12 and obtains the result that the four independent variables affect the Earning Press Share simultaneously, this explains. The dominant influence that is owned by the variables Return On Assets (ROA), Return On Equity (ROE), Net Interest Margin (NIM), Loan To Deposit Ratio (LDR), on the company's Earning Per Share (EPS) can be used as a consideration for companies both issuers and investors to predict earnings per share and improve financial performance.